2016
DOI: 10.7160/aol.2016.080307
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Business Informatics Specifics in Agricultural Enterprises

Abstract: Presented paper deals with analysis and identification of business informatics specifics in agricultural enterprises in the Czech Republic farming at land of size up to 500 hectares. The study is based on thorough review of literature about latest issues in agriculture business informatics. There is a follow up to certain results of previous research on business informatics in agriculture that was conducted by authors in 2013. The analysis has brought findings that business informatics has several peculiaritie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 22 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…We found that on the global interconnectedness level, the use of Internet fosters the flow of information internationally, flattens the world economy, and supports the participation of small businesses and start-ups in the global market (Eze et al, 2018;Yuldinawati et al, 2018). Entrepreneurs have benefited from having unlimited access to digital information sources in terms of performance and development (Kubata & Simek, 2016), opportunity recognition (Tuomisalo, 2019), personal and business growth (Ahmad et al, 2020), scanning environment for accessing information (Haase & Franco, 2011), and further encouraging their long-term learning process (Dulle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We found that on the global interconnectedness level, the use of Internet fosters the flow of information internationally, flattens the world economy, and supports the participation of small businesses and start-ups in the global market (Eze et al, 2018;Yuldinawati et al, 2018). Entrepreneurs have benefited from having unlimited access to digital information sources in terms of performance and development (Kubata & Simek, 2016), opportunity recognition (Tuomisalo, 2019), personal and business growth (Ahmad et al, 2020), scanning environment for accessing information (Haase & Franco, 2011), and further encouraging their long-term learning process (Dulle et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Tuomisalo (2019) argued that opportunity recognition is fundamentally resulted from ISB in the context of telecommunication multinational enterprises. Other scholars like Dulle et al (2017), Kubata and Simek (2016), Molnár and Bernat (2007), and Savarese et al (2016), highlighted the impact of information access on entrepreneurial development and business growth. While Kubata and Simek (2016) emphasized on the importance and the role of entrepreneur's information behavior in business growth, Dulle et al (2017), raised their concerns about entrepreneurs' lack of critical literacies in information access, retrieval, and entrepreneurs' ISB, in general.…”
Section: Sub-conversation 2: Entrepreneurs' Information Accessmentioning
confidence: 99%
See 1 more Smart Citation